AGRICULTURA FAMILIAR E DESENVOLVIMENTO RURAL: CENÁRIOS CONTEMPORÂNEOS E QUESTÕES EM DEBATE - Matte, Alessandra; Schervinski Villwock, Ana Paula; Fornazier, Armando; Wagner, Danielle; Fossá, Juliano Luiz (Revista Grifos, 2022)
.